Pengaruh Human Resources, Work Motivation, dan Job Satisfaction Terhadap Kinerja Pegawai (Studi Kasus PT. BPRS Mitra Mentari Sejahtera) - Ervianti, Vika; Riawan, Riawan (Universitas Islam Nahdlatul Ulama Jepara, 2025)
PT. BPRS Mitra Mentari Sejahtera, as a sharia financial institution, faces various challenges in improving service quality, competitiveness, and productivity. Some of the main obstacles include a lack of work motivation, dissatisfaction with the work environment, and a gap between employee skills and job demands. Therefore, this study aims to analyze the influence of human resource quality, work motivation, and job satisfaction on employee performance. Using a quantitative approach and purposive sampling method, this study involved 58 respondents from PT. BPRS Mitra Mentari Sejahtera Ponorogo. The results show that human resource quality significantly influences work motivation, which ultimately enhances job satisfaction and employee performance. Additionally, work motivation has a direct positive impact on both job satisfaction and employee performance. As a managerial implication, the company is advised to strengthen employee collaboration through team programs that promote effective communication and build trust. For future research, it is recommended to explore other factors that may influence employee motivation and performance, such as organizational culture, leadership style, and economic conditions.